Action and therapeutic targets of folliculin interacting protein 1: a novel signaling mechanism in redox regulation - Ran, Qingzhi; Li, Aoshuang; Yao, Bo; Xiang, Chunrong; Qu, Chunyi; Zhang, Yongkang; He, Xuanhui; Chen, Hengwen (Frontiers in Cell and Developmental Biology, 2025)
Rapid activation of adenosine monophosphate-activated protein kinase (AMPK) induces phosphorylation of mitochondrial-associated proteins, a process by which phosphate groups are added to regulate mitochondrial function, thereby modulating mitochondrial energy metabolism, triggering an acute metabolic response, and sustaining metabolic adaptation through transcriptional regulation. AMPK directly phosphorylates folliculin interacting protein 1 (FNIP1), leading to the nuclear translocation of transcription factor EB (TFEB) in response to mitochondrial functions. While mitochondrial function is tightly linked to finely-tuned energy-sensing mobility, FNIP1 plays critical roles in glucose transport and sensing, mitochondrial autophagy, cellular stress response, and muscle fiber contraction. Consequently, FNIP1 emerges as a promising novel target for addressing aberrant mitochondrial energy metabolism. Recent evidence indicates that FNIP1 is implicated in mitochondrial biology through various pathways, including AMPK, mTOR, and ubiquitination, which regulate mitochondrial autophagy, oxidative stress responses, and skeletal muscle contraction. Nonetheless, there is a dearth of literature discussing the physiological mechanism of action of FNIP1 as a novel therapeutic target. This review outlines how FNIP1 regulates metabolic-related signaling pathways and enzyme activities, such as modulating mitochondrial energy metabolism, catalytic activity of metabolic enzymes, and the homeostasis of metabolic products, thereby controlling cellular function and fate in different contexts. Our focus will be on elucidating how these metabolite-mediated signaling pathways regulate physiological processes and inflammatory diseases.